Design Of An Educational Game For Introducing Flat Shapes To 4th Grade Elementary Students At Sdn Temugiring Using Construct 2 - Muhammad Ardiansyah; Ahmad Munawir; Wahyu Amaldi (PT ARRUS Intelektual Indonesia, 2025)
This study aims to design and develop an educational game that serves as an interactive learning medium to introduce the concept of flat shapes to fourth-grade students at SDN Temugiring. In elementary school mathematics, especially on the topic of flat shapes, many students still face difficulties in understanding the forms and characteristics of each shape. Therefore, the use of interactive learning media in the form of educational games is expected to provide a more enjoyable and engaging learning experience for students. The development of this game follows the Multimedia Development Life Cycle (MDLC) method, which consists of several stages: concept formulation, design, material collection, production, testing, and distribution. The game application was developed using Construct 2, as this platform offers an easy-to-understand interface and supports the development of 2D-based games. The results of the study show that this educational game successfully enhances students’ understanding of flat shape material and positively impacts their learning motivation in the classroom.